Xylooligosaccharide-mediated gut microbiota enhances gut barrier and modulates gut immunity associated with alterations of biological processes in a pig model. (15th October 2022) - Tang, Shanlong; Chen, Yuxia; Deng, Fuli; Yan, Xiaowei; Zhong, Ruqing; Meng, Qingshi; Liu, Lei; Zhao, Yong; Zhang, Sheng; Chen, Liang; Zhang, Hongfu
Abstract: Xylooligosaccharide (XOS) has tremendous prebiotic potentials for gut health, but the relevant mechanisms are unclear. Herein, we confirmed the positive effects of dietary XOS enhancing gut barrier in a pig model via suppressing the expression of pro-inflammatory cytokines ( IL-6 and IL-8 ). Meanwhile, XOS increased beneficial microbes Lactobacillus and decreased potential pathogenic bacteria. Moreover, XOS augmented microbiota-derived metabolites (mainly butyrate, propionate, and secondary bile acid) to strengthen the gut barrier and regulate gut immunity through activating host G-protein coupled receptors 109a or inhibiting histone deacetylases. Furthermore, XOS attenuated IgA-production and antigen cross-presentation processes. In addition, XOS supplementation led to the alteration of cell proliferation, remodeling of the energy metabolism, activation processes of serial genes or proteins, increased molecular chaperones, and the enhanced ubiquitin-proteasome pathway in cecal cells. Collectively, these results suggest that XOS enhances gut barrier and modulates gut immunity by optimizing gut microbiota and their metabolites, which is associated with alterations of biological processes. Graphical abstract: Unlabelled Image